Effect of production systems on the performance of dairy cows in the Gezira State, Sudan - Elobied, G. H.; Dafalla, A.A; A.Abdalla, Asma; Mohammed, Imtithal; Fadiel, Aziza; Abdalla, Isam (Gezira Journal of Agricultural Science, 2017)
This study was conducted in the Gezira State, Sudan, with the objectives of investigating and comparing the  effect of production  systems  on age  at first calving, calving interval, milk yield, herd structure, mortality and growth rate in traditional animal production and organized dairy farms. Six out of eight localities were included in the study. From each locality, 5 herds, each of traditional animal production and organized dairy farms were selected. This survey was carried out  using questionnaire involving 40 farmers (including the surveyed farms) from each locality. Means and standard deviations for each studied parameter were calculated using SPSS. The result revealed greater differences in the studied parameters between the two systems of production. Feed had a great influence on animal performance. It could be recommended that, for improving the traditional farm performance, efforts should be payed  to upgrade animal genetics through selection from highly producing local cows and introduction of foreign breeds. Feeding improvement in both terms of quality and quantity is also needed. اجريت هذه الدراسة  بولاية الجزيرة بغرض التعرف ومقارنة أثر نظم الانتاج المختلفة علي العمر عند اول ولادة والفترة بين الولدتين وانتاج اللبن وتركيب القطيع والنفوق ومعدل النمو في كل من قطاع الانتاج الحيواني التقليدي ومزارع الالبان المنتظمة . شملت الدراسة ستة من ثمانية محليات. اختير من كل محلية 5 قطعان من كل من قطاع الانتاج الحيواني التقليدي ومزاع الالبان المنتظمة. دعم المسح باستبيان شمل 40 مزارع من كل محلية. حسبت المتوسطات والانحرافات المعيارية لكل عنصر من عناصر الدراسة وذلك باستخدام نظام الحزم الاحصائية للعلوم الاجتماعية (  (SPSS  كشفت الدراسة عن فروقات معنوية بين العناصر المدروسة في كل من النظاميين واكدت ان الغذاء له اثر كبير علي اداء الحيوان وكذلك العناصر الأخرى خاصة الوراثية قد يكون لها اثر علي الاداء. من اجل تحسين مزارع الانتاج الحيواني التقليدي توصي الدراسة تبذل مجهودات لرفع الكفاءة الوراثية للحيوان  من خلال الاختيار من الابقار المحلية العالية  الانتاج وادخال السلالات الاجنبية . أيضاً يجب رفع مستوي الغذاء من الناحية الكمية والنوعية.